2014
DOI: 10.1089/ars.2014.5856
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Responsive MicroRNA-101 Promotes Angiogenesis via Heme Oxygenase-1/Vascular Endothelial Growth Factor Axis by Targeting Cullin 3

Abstract: Aims: Hypoxia induces expression of various genes and microRNAs (miRs) that regulate angiogenesis and vascular function. In this study, we investigated a new functional role of new hypoxia-responsive miR-101 in angiogenesis and its underlying mechanism for regulating heme oxygenase-1 (HO-1) and vascular endothelial growth factor (VEGF) expression. Results: We found that hypoxia induced miR-101, which binds to the 3¢untranslated region of cullin 3 (Cul3) and stabilizes nuclear factor erythroid-derived 2-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 61 publications
3
52
0
Order By: Relevance
“…In this study, we consistently found that the expression of miR-101a was down-regulated in post-infarct rat hearts and cultured neonatal CFs treated with hypoxia. In contrast, a recent study [33] demonstrated that miR-101 was increased in human umbilical vein endothelial cells (HUVECs) exposed to hypoxic conditions and stimulated angiogenesis as a means of improving post-ischemic vascular remodeling in mouse ischemic hind limbs. These results suggest that hypoxia-induced expression of miR-101 may depend on the cell type involved.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we consistently found that the expression of miR-101a was down-regulated in post-infarct rat hearts and cultured neonatal CFs treated with hypoxia. In contrast, a recent study [33] demonstrated that miR-101 was increased in human umbilical vein endothelial cells (HUVECs) exposed to hypoxic conditions and stimulated angiogenesis as a means of improving post-ischemic vascular remodeling in mouse ischemic hind limbs. These results suggest that hypoxia-induced expression of miR-101 may depend on the cell type involved.…”
Section: Discussionmentioning
confidence: 98%
“…For example, several miRs ( e.g., miR-155) can potentially activate HO-1 expression through the downregulation of the transcriptional repressor Bach1. 171173 Additionally, miR-101 promoted HO-1 expression by targeting the Cullin 3: E3 ubiquitin ligase, resulting in Nrf2 stabilization, 174 whereas miR-200a promoted Nrf2 activation by targeting its cytoplasmic anchor Keap-1. 175 …”
Section: Regulation Of Heme Oxygenase Gene Expressionmentioning
confidence: 99%
“…Furthermore, this study demonstrates that Nrf2 activation consequently inhibits the anchorage-independent growth of breast cancer cells in vitro and carcinogen-induced mammary hyperplasia in vivo. Cul3 is an important component of the Keap-1 protein complex that promotes Keap1-dependent Nrf2 ubiquitination and proteasomal degradation [112]. Kim et al demonstrated that Cul3 is a target of miR-101.…”
Section: Interaction Of Mirnas and The Keap1-nrf2 Signaling Pathwaymentioning
confidence: 99%